New hot isostatic pressing (HIP) simulation method with taking into account of the operating cycle ramp - Redouani, L.; Boudrahem, S.; Alem, S. (International journal of advanced manufacturing technology, 2019)
Hot isostatic pressing (HIP) is a process that allows producing full dense materials with high mechanical properties. The simulation work undertaken on this subject does not take into account the densification which operating during the rise in pressure and temperature. In this paper, we propose a new method for HIP simulations by considering the powder densification, which operating during the rise in pressure and in temperature. Experiments were performed using tungsten powders by varying the parameters of the used HIP cycles. The obtained results are in good agreement with the simulations predictions, especially when pressures exceed 200 MPa. They clearly show that an important part of the powders densification can reach in some cases 88% during the cycles rise. This approach is very interesting for the number of tuning tests reduction and for the implementation prices improvement.